FRI0628 Ultrasound shows signs of inflammation in most patients with rheumatoid arthritis in longstanding clinical remission, irrespective of conventional synthetic or biologic dmard therapy. (15th June 2017) - Møller, U Døhn; Brahe, CH; Hetland, ML; Fana, V; Krabbe, S; Ammitzbøll-Danielsen, M; Østergaard, M; Terslev, L
Abstract : Background: None of the currently accepted remission criteria in rheumatoid arthritis (RA) incorporate inflammation on imaging. Signs of inflammation on ultrasound (US) and magnetic resonance imaging are frequently seen in RA patients in clinical remission.(1–3) It is not known whether patients in longstanding clinical and radiographic remission obtained through a DAS28 driven treat to target (T2T) strategy by conventional synthetic disease modifying anti-rheumatic drugs (csDMARD) or by biologic (bDMARD) therapy differ with respect to US detected synovitis. Objectives: In RA patients in longstanding clinical and radiographic remission, achieved by a DAS28-driven T2T strategy, to investigate if US signs of inflammation differs between RA patients, treated with csDMARD or bDMARD (+/- csDMARD). Methods: Eighty-seven patients with RA in longstanding clinical (continuous DAS28<2.6 for the preceding year) and radiographic (no progression for at least 1 year) remission, were included in the study. US of elbows, wrists, MCP2–5, knees, ankles and MTP2–5 were performed using a GE LOGIQE9 US unit. Each joint was scored for grey-scale synovitis (GSS) and synovial color Doppler activity (CDA) by a 0–3 semi-quantitative score. Ultrasound remission was defined in two ways: either no (GSS=0 and CDA=0) or minimal (GSS≤1 and CDA=0) inflammation in any of the 24 assessed joints. Results: Clinical characteristics and US findings are shown in the table. All 87 patients fulfilled DAS28 remission criteria at entry and CDAI remission was fulfilled in 76% and 79% in the csDMARD and bDMARD group, respectively. Complete absence of any signs of US inflammation (GSS=0 and CDA=0) was seen in 0% and 14% in the csDMARD and bDMARD groups, respectively (p=0.01), while minimal US inflammation (GSS≤1 and CDA=0) was seen in 33% and 40% (NS). CDA in at least one joint was seen in the majority of patients in both groups, 58% and 57% respectively. Conclusions: The majority of RA patients, in this cohort of patients in longstanding clinical and radiographic remission obtained through a DAS28 driven T2T strategy, had signs of inflammation as assessed by US, irrespective of receiving biologic treatment or not. For patients in clinical remission, the consequences of sustained US inflammation still have to be investigated. References: Brown AK et al.: Arthritis Rheum 2006;54(12):3761–73. Saleem B et al.: Arthritis Rheum 2009;60(7):1915–22. Gandjbakhch F et al.: J Rheumatol 2011;38(9):2039–44. Disclosure of Interest: None declared